Accordion effect: A red herring during percutaneous angioplasty of arteriovenous dialysis access. Issue 4 (July 2021) - Rao, Indu Ramachandra; Paramasivam, Ganesh; Devasia, Tom; Prabhu, Attur Ravindra; Nagaraju, Shankar Prasad
Accordion or concertina effect is the angiographic appearance of pseudostenosis caused by interaction of a stiff guidewire with a tortuous vessel during endovascular procedures. This phenomenon may often mislead the interventionist into performing unnecessary and potentially harmful procedures in a bid to treat the 'stenotic' lesion. The resolution of 'stenosis' on withdrawal of the guidewire clinches the diagnosis. While well described in coronary vessels, the occurrence of this phenomenon in arteriovenous fistula or graft has not been reported. We describe a case of accordion effect observed during endovascular intervention for arteriovenous graft salvage.